Research on the Design of Intelligent Voice Interaction System Based on Affective Computing - Sun, Jialin (International Scientific Technical and Economic Research, 2025)
With the rapid development of intelligent voice technology, traditional voice interaction systems have gradually been unable to meet users’ needs for emotional interaction. To improve the naturalness and humanity of human-computer interaction, this study proposed and designed an intelligent voice interaction system based on emotional computing. The system accurately analyzes the user’s emotional state through emotion recognition technology and combines speech synthesis technology to generate voice feedback that meets the user’s emotional needs. The study first discussed the relevant technologies of emotion computing and voice interaction in detail, designed the system architecture, and implemented emotion recognition and speech generation algorithms. Through experimental evaluation and user feedback analysis, the superiority of the system in emotion recognition accuracy, voice interaction effect, and user experience were verified. Compared with traditional voice interaction systems, the system of this study significantly improved the user’s emotional resonance and interaction satisfaction, reflecting the practical application value of emotion computing in voice interaction. Finally, the study discussed the limitations and future development directions of the system and proposed the possibilities and challenges for the further development of emotion computing and voice interaction.